Early Starter Vs Late Starter In Learning English As Foreign Language - Juwita, Anggun; Harahap, Nadia Hawalinda; Jumiati, Tri; Hilpina, Vaiza; Pebria, Elsa; Lastaria, Parma (Journal Of Language Education and Development (JLed), 2024)
Language learning is related to the first language and to the second language. (Meilan, A:2014). The process of acquiring a second language can be influenced by natural process, social, motivation and language attitude. Moreover, language can be acquired through education and learning. It is debatable topics that age has an important role in learning language. Some initial studies found that children are in the critical period, therefore they can learn and acquire language faster. However, some initial studies found that the decline in students' memory is related to age. Age is not a measure of success in mastering a second/foreign language other than the mother tongue, as long as the person has the desire to use the foreign language or second language for integration and socialization purposes.